Modern designs: history and memory in Le Corbusier’s Chandigarh - Ghosh, Nabaparna (Journal of Architecture and Urbanism, 2016)
Located at the foothills of the Sivalik Mountains, Chandigarh was the dream city of independent India’s first Prime Minister Jawaharlal Nehru. In 1952, Nehru commissioned the Swiss-French architect Le Corbusier to design Chandigarh. Scholars often locate in Corbusier’s plans an urban modernity that required a break with the past. Moving away from such scholarship, this article will argue that Chandigarh marked a climactic moment in Le Corbusier’s career when he tried to weave together modern architecture with tradition, and through it, human beings with nature. A careful study of the cosmic iconography of Chandigarh clearly reveals that nature for Le Corbusier was more than a vast expanse of greenery: it was organized in symbolic ways, as a cosmic form emblematic of Hindu mythologies. I will argue that in addition to local conditions – economic and cultural – that impacted the actual execution of Le Corbusier’s plans, cosmic iconography shaped a modernism profoundly reliant on Hindu traditions. This iconography also inspired a new generation of Indian architects like Balkrishna Vithaldas Doshi (1927 – present). Doshi played a key role in authoring the postcolonial architectural discourse in India. Following Le Corbusier, he advocated an architectural modernism anchored in sacred Hindu traditions.